High oxygen treatment increases antioxidant capacity and postharvest life of strawberry fruit - Ayala-Zavala, J. Fernando; Wang, Shiow Y.; Wang, Chien Y.; González-Aguilar, Gustavo A. (2007)
The antioxidant capacity, total phenolics, volatile compounds, and postharvest quality of strawberry fruit were evaluated after storage in high oxygen atmospheres (40, 60, 80, and 100 kPa) during 14 days at 5 °C. Strawberries stored at high oxygen atmospheres (>40 kPa) showed higher antioxidant capacity, total phenolics, less decay, and longer postharvest life than those stored in air. Fruit stored under high oxygen atmospheres generally emitted lower levels of volatile compounds than those stored in air. However, individual volatile compounds were affected differently. While the emission of most volatiles decreased under high oxygen atmospheres during storage, the production of some volatile compounds such as methyl acetate and methyl hexanoate increased. In conclusion, strawberries stored under superatmospheric oxygen conditions maintained higher levels of antioxidant capacity but retained lower levels of volatile production than those stored in air
Bibliografija: 30 jed
Keywords: Jagoda -- Antioksidansi